RESULTS OF OBSERVATIONS OF SELECTED ASTEROIDS AT THE NEW TELESCOPE MOBITEL OF NAO IN 2011-12 - Ivantsov, A.; Pomazan, A.; Kryuchkovski, V.; Gudkova, L. (Одеські астрономічні публікації, 2012)
The results of position observations of selected asteroids with the new telescope Mobitel of NAO are presented. The possibility of using them for contemporary problems is discussed.